2014
DOI: 10.1002/bdd.1925
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypertonic buffer composition on lymph node uptake and bioavailability of rituximab, after subcutaneous administration

Abstract: Subcutaneous administration of biologics is highly desirable; however, incomplete bioavailability after sc administration remains a major challenge. In this work we investigated the effects of excipient dependent hyper-osmolarity on lymphatic uptake and plasma exposure of rituximab as a model protein. Using Swiss Webster (SW) mice as our animal model, we compared the effects of NaCl, mannitol and, O-Phospho-L-Serine (OPLS) on plasma concentration of rituximab over 5 days after sc administration. We observed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…In our own work, we found a relationship between increased buffer tonicity and improved bioavailability of subcutaneously administered rituximab in a mouse model . Furthermore, our data suggest that the effect of buffer hypertonicity on rituximab bioavailability is excipient specific.…”
Section: Barrier To Sc Absorption Of Protein Therapeuticssupporting
confidence: 53%
See 3 more Smart Citations
“…In our own work, we found a relationship between increased buffer tonicity and improved bioavailability of subcutaneously administered rituximab in a mouse model . Furthermore, our data suggest that the effect of buffer hypertonicity on rituximab bioavailability is excipient specific.…”
Section: Barrier To Sc Absorption Of Protein Therapeuticssupporting
confidence: 53%
“…4,24 In our own work, we found a relationship between increased buffer tonicity and improved bioavailability of subcutaneously administered rituximab in a mouse model. 25 Furthermore, our data suggest that the effect of buffer hypertonicity on rituximab bioavailability is excipient specific. We found that mannitol, a neutral excipient, performed better than the negatively charged O-phospho-L-serine at equal tonicities.…”
Section: Uptake By the Lymphaticsmentioning
confidence: 72%
See 2 more Smart Citations
“…Recently, it is reported that formulation may also affect the bioavailability of SC administered protein therapeutics. Fathallah et al [30] have described a significant increase in the bioavailability of SC administered rituximab when administered in a hypertonic buffer solution, because of an increase in the amount of protein that traffics through the lymph system.…”
Section: Pharmacokinetic Considerationsmentioning
confidence: 99%